Selective Removal of Arsenic and Antimony from Pb-Ag Sulfide Concentrates by Alkaline Leaching: Thermodynamic and Kinetic Studies - Walter Blanco-Vino; Gerardo Zamora; Javier I. Ordóñez (Mining, 2024)
Arsenic and antimony are impurities that reduce the economic value of concentrates due to the environmental problems they cause. The removal of these impurities by hydrometallurgical means has been highly studied for sulfide copper concentrates using different leaching agents in an alkaline medium (NaClO, H2O2, NaOH, Na2S, NaHS, and S). For a lead–silver concentrate consisting of galena, sphalerite, and pyrite, it was possible to selectively reduce the arsenic content from 1.10% to 0.55% and antimony from 2.41 to 1.04% through the digestion-leaching technique that uses elemental sulfur as a leaching agent in alkaline medium. The adequate powdered sulfur and sodium hydroxide dosage were 336 and 342 kg/t, respectively. The process was carried out at 120 °C with a liquid/solid ratio of 2 in digestion and 5.67 in leaching; the appropriate digestion and leaching time were 20 and 30 min, respectively. The thermodynamics and kinetics of this process turned out to be very complex due to the great variety of simultaneous leaching and precipitation reactions. The digestion process exhibited a mixed kinetic control, where diffusion through the boundary layer and the chemical reaction were the controlling steps with an activation energy of 11.05 kcal/mol.